Dinámica poblacional de Cosmopolites sordidus (Germ., 1824) (Col.: Curculionidae) en bananales del cv. Prata (Grupo AAB), en Alfredo Chaves, Espírito Santo - Arleu, R.J; Neto, S.S; Gomes, J.A; Nobrega, A.C; Scardini, D.M (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
This experiment was carried out in Alfredo Chaves, Espirito Santo State, Brazil, with the cultivar Prata, front 1977 to 1982, in order to study the effect of climatic elements on the movement of the adult Cosmopolites sordidus (Germ , 1824) and its population tendency in a banana plantation. Adult population was evaluated utilizing pseudostem baits from the meter of pseudostem. conclusions were. C. sordidus adults had a constant moyenzent throughout the year, climatic elements had no influence on the population fluctuation, there was a decrescent population tendency during the time of the experiment, perhaps due to the utilized practice.